Determinants of equity pension plan flows - Martí Ballester, Carmen Pilar (Estudios de Economía, 2014)
The aim of this study is to analyze investor response to different measures of pension plan performance. To do this, we implement a fixed effects panel data methodology corrected by heteroskedasticity, serial correlation and cross-sectional dependence, as proposed by Vogelsang (2012). The results obtained show that investors make their decision to invest in a specific pension plan depending on past returns and the type of management company administering the plan. On analyzing the flow-performance relationship for each type of management company we find that both types of companies can differ in the information provided to investors and in their marketing strategies and services for attracting clients.